The impact modernisation of land administration on two Malay classes in Kedah, 1909-1941 - Mohd Rus, Ahmad Kamal Ariffin; Nordin, Nurizwanfaizi (2014)
Since traditional times, the Malays of Kedah had developed an organized system and method of administration of land affairs. The traditional land laws used by the Kedah Malay government, based on Islamic and local elements, brought about stability and strengthened the patron-client ties between the ruling and ruled classes. With the existence of clear strata in traditional Kedah Malay society, land administration also reflected this difference in the context of traditional ruling class policy on the two classes in this society.The traditional-era Kedah government practiced a dualistic policy1 in regards to land, and created a discriminative value in land administration.Interestingly, when the British took over Kedah through the 1909 Bangkok Treaty, this policy remained.In examining the dualistic policy in regards to land administration, it has not been the focus of discussion in most academic literature. In 1976, Lim Teck Ghee produced a classic title “Origins of a Colonial Economy, Land and Agriculture in Perak 1874-1897”.This study discusses how the British introduced a new and modern land system in Perak after it took over control of the state in 1874.Lim Teck Ghee explained in his book a number of aspects in the land law schemes in Perak that paved the way to mass land-clearing for colonial commercial economic purposes. As the author focused on land in regards to the free market economy, any dualistic policy that existed among the Perak Malays was not highlighted.In 1985, Ahmad Nazri Abdullah published his research topic “Melayu dan Tanah”.This study focuses on the formation and implementation of the Malay Reservations Enactment since it was passed in 1913.Ahmad Nazri Abdullah’s research focuses on the Malays residing in the Federated Malay States (FMS).The main theme of this study is the issue of formation and enforcement of the Malay Reservations Enactment. Again, the dualistic policy among the Malays was not discussed in the study.In the context of Kedah, the continuation of the implementation of traditional-era dualistic policy during the colonial period is a unique element, in that it shows British compromise in preserving this heritage.This situation is not surprising, judging from British previous policy in its Malay protectorates by taking a cautious approach in regards to Malay sentiments. Frank Athelstane Swettenham, that grand imperialist of Malaya, stated that: “We should not interfere overmuch with native customs and prejudices, and we should be specially careful to avoid any attempt to force English views, even when English opinion is practically unanimous on a subject, upon a people living utterly under different conditions…” This paper attempts to see how far British dualistic policy regarding land impacted Malay society in 1909-1941.This study will also identify the factor in the preservation of this Malay elite privilege during the colonial period. This dualistic policy could also explain why the lower-class Kedah Malays failed to achieve a better standard of living even after the modernisation of land administration.